2022
DOI: 10.34305/jnpe.v3i01.612
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Penerapan Metode Penugasan Tim Dan Komunikasi Efektif Dengan Kepuasan Kerja Perawat Di Instalasi Rawat Inap Rumah Sakit Umum Daerah 45 Kuningan Tahun 2022

Abstract: Metode tim dan komunikasi efektif selain dapat meningkatkan kualitas pelayanan juga dapat meningkatkan kepuasan kerja perawat. Penelitian ini bertujuan untuk menganalisis hubungan penerapan metode penugasan tim dan komunikasi efektif dengan kepuasan kerja perawat RSUD 45 Kabupaten Kuningan Tahun 2022. Metode analitik kuantitatif dengan rancangan jenis penelitian korelasional dan pendekatan cross sectional. Populasi sebanyak 153 perawat di RSUD 45 Kuningan, berdasarkan purposive sampling sebanyak 110 perawat. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on research data, the average respondent feels quite satisfied with several job satisfaction indicators that already exist at RSUD Dr. M.M Dunda, such as job indicators themselves, salary indicators/work incentives, as well as research results at Sitti Rahmah Hospital in Padang, also stated that salary is the most significant factor that will influence job satisfaction, in fact salary contributes to more staff (Murni et al al., 2022), position/career promotion is the basis for nursing management to increase activities related to promotion, especially in aspects of career path, and indicators of the work atmosphere and environment as well as relationships between colleagues, such as research by Rusmianingsih et al, 2022) who found that interaction between co-workers and nurses can increase satisfaction at work, thereby creating a comfortable work environment. This is supported by previous research on nurses who also stated that when they were working and faced with situations and conditions in their workspace that forced them to be independent, they were able to do so.…”
Section: Job Satisfaction Of Inpatient Nursesmentioning
confidence: 99%
“…Based on research data, the average respondent feels quite satisfied with several job satisfaction indicators that already exist at RSUD Dr. M.M Dunda, such as job indicators themselves, salary indicators/work incentives, as well as research results at Sitti Rahmah Hospital in Padang, also stated that salary is the most significant factor that will influence job satisfaction, in fact salary contributes to more staff (Murni et al al., 2022), position/career promotion is the basis for nursing management to increase activities related to promotion, especially in aspects of career path, and indicators of the work atmosphere and environment as well as relationships between colleagues, such as research by Rusmianingsih et al, 2022) who found that interaction between co-workers and nurses can increase satisfaction at work, thereby creating a comfortable work environment. This is supported by previous research on nurses who also stated that when they were working and faced with situations and conditions in their workspace that forced them to be independent, they were able to do so.…”
Section: Job Satisfaction Of Inpatient Nursesmentioning
confidence: 99%
“…Metode Tim adalah pemberian asuhan keperawatan yang melibatkan tim yang professional dan tehnikal bertanggung jawab untuk berkoordinasi selama dinas dalam satu shift, (Rusmianingsih et al, 2022). Penerapan metode tim dapat meningkatkan kepuasan kerja perawat, metode tim dapat meningkatkan kepuasan kerja perawat dalam memberikan asuhan keperawatan yaitu kelebihan metode tim seperti komunikasi efektif dengan dua kepemimpinan yaitu kepala ruangan dan ketua tim dalam penerapan metode tim membuat kerja sama tim meningkat secara otomatis meningkatkan kepuasan kerja perawat pelaksana (Pelealu et al, 2022).…”
Section: Pembahasanunclassified
“…Agar pelayanan keperawatan dapat berjalan dengan optimal maka perawat sangat berpengaruh terutama dalam memberikan pelayanan dimana perawat sebagai ujung tombak karena langsung berhubungan dengan pasien. 2 Maka dijelaskan oleh para ahli yaitu menurut Donsu (2017), motivasi berasal dari kata motif yang berarti dorongan atau alasan.Motivasi merupakan tenaga pendorong yang mendorong manusia untuk bertindak atau suatu tenaga di dalam diri manusia, yang menyebabkan manusia bertindak atau melakukan sesuatu. 3 Dampak yang terjadi akibat rendahnya motivasi terhadap kepuasan kerja perawat jika mengalami penurunan kinerja.…”
Section: Pendahuluanunclassified